LBDNet inter-laboratory comparison at high doses of ionizing radiation using the dicentric plus caffeine assay - Romero Aguilera, Ivonne (2025)
Purpose: To assess the performance of the LBDNet laboratories in estimating dose over 5Gy of ionizing radiation using the dicentric chromosome plus caffeine assay. Materials and methods: Dose-response curve fitting: Peripheral blood was irradiated in vitro between 5 and 25Gy. Then, the DC plus caffeine assay was carried out. Thirteen laboratories received and analyzed metaphase images. The linear dose-response curve was fitted for each laboratory. Dose estimation was performed analyzing coded metaphase images from three different irradiated samples (7.5, 15, 20Gy) and using the fitted curve from every laboratory. Results: The dose estimation accuracy was within the expected dose ranges. The 76.9%, 84.6% and 69.2% of the estimated doses fell into the ± 20% of the true radiation dose. The 92.3%, 92.3%, and 61.5% of the 95% of the confidence interval of the estimated doses included the true radiation dose. The trueness was 0.9%, 4.4% and 9.6%. The Coefficients of Variation of the estimated doses were 14.5%, 16.1% and 17.8%. Results from only one laboratory were deemed questionable for dose estimation, based on the Z-score derived from robust methods. Conclusion: The intercomparison study yielded satisfactory results; however, dose estimation accuracy tended to decrease, and variability between laboratory results increased as the dose level rose.